Seventy-two beats a second / Iman Karmyla Shahrul Idzwan and Sumarni Maulan - Shahrul Idzwan, Iman Karmyla; Maulan, Sumarni (Academy of Language Studies, 2023)
Poetry is known by many for its creative construction of ideas written in stylistic sentences with meaning for readers to infer. Initially this project intended to share written poems, with the theme of universal love, on social media but was later developed to achieve the following objectives; to publish a collection of poems on TikTok, to publish a book of poems based on posts from TikTok, and to determine viewers' perceptions of the posted poetry. The project went through 4 phases which are TikTok account creation and poem posting, poetry book publication, questionnaire development and administration, and TikTok analysis. All objectives were achieved by which a collection of poems was successfully posted on TikTok and a poetry book entitled “Seventy Two Beats A Second” was published. The survey results show that people do enjoy reading and writing poetry however they do not share their poems but are interested in what others have written stating that they are interested to buy a physical book of the poems posted on TikTok. The project hopes that aspiring poets would find the confidence in themselves to publish their poems as well as to serve as evidence that writing and sharing poems can be a successful career or at least serve as a path to express one’s feeling and emotion.